2015
DOI: 10.1063/1.4905730
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Maxwell's fish-eye dynamics in elastic plates

Abstract: We experimentally demonstrate that a Duraluminium thin plate with a thickness profile varying radially in a piecewise constant fashion as h(r) = h(0)(1 + (r/Rmax)2 ) 2 , with h(0) = 0.5 mm, h(Rmax) = 2 mm and Rmax = 10 cm behaves in many ways as Maxwell's fish-eye lens in optics, since its imaging properties for a Gaussian pulse with central frequencies 30 kHz and 60 kHz are very similar to those predicted by ray trajectories (great circles) on a virtual sphere (rays emanating from the North pole meet at the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…This approach has been validated for adiabatically varying thickness, for example, for the design of elastic lenses. [ 49–51 ] Here, we demonstrate that, in contrast to an adiabatically varying thickness, a periodic change of plate thickness on a subwavelength scale can be utilized to design effective anisotropic metamaterials for flexural waves. A significant advantage in terms of realization is that a single material is required and that the subwavelength structuration is easily implemented by surface machining or, more conveniently, by 3D printing, a technique now readily available for many types of materials, including ceramics and metals.…”
Section: Waveshiftermentioning
confidence: 97%
See 1 more Smart Citation
“…This approach has been validated for adiabatically varying thickness, for example, for the design of elastic lenses. [ 49–51 ] Here, we demonstrate that, in contrast to an adiabatically varying thickness, a periodic change of plate thickness on a subwavelength scale can be utilized to design effective anisotropic metamaterials for flexural waves. A significant advantage in terms of realization is that a single material is required and that the subwavelength structuration is easily implemented by surface machining or, more conveniently, by 3D printing, a technique now readily available for many types of materials, including ceramics and metals.…”
Section: Waveshiftermentioning
confidence: 97%
“…Keeping all elastic parameters constant, the rigidity for each layer, D a and D b , is easily implemented by adjusting the thickness, h a and h b , of the plate at each layer, following the definition of D . [ 21,49–51 ] According to Equation (5), the thickness difference h a − h b increases steeply for θ above 40° (see Figure S1, Supporting Information). We therefore choose for the experimental realization an angle θ = 20°, in order to limit the geometrical constraints for the 3D‐printing.…”
Section: Waveshiftermentioning
confidence: 99%
“…Generally, one can implement a variety of technologies in order to create a refractive index profile that performs fisheye focusing e.g. thin plates 4 , holy parallel plates 5 . In this paper we take a different approach in which fisheye principle is realized using the mode theory of a parallel-plate waveguide 6 .…”
Section: Maxwell Fisheye Lens Design Principlesmentioning
confidence: 99%
“…This method is referred to as focusing and allows users to generate high-amplitude signals at the "hot spot," thus improving the signal-to-noise ratio in pitch-catch and pulse-echo methods used for damage quantification. Lamb wave mode focusing can be achieved using gradient-index phononic crystals [2][3][4][5][6][7] or locally resonant metamaterials, [8][9][10] phased-array beamforming, [11][12][13][14] dispersion-compensated actuation, 15 and plano-concave slice lenses. 16 Wu et al numerically demonstrated focusing of the A0 mode of Lamb waves in a gradient-index phononic crystal.…”
Section: Introductionmentioning
confidence: 99%
“…20 Lefebvre et al performed experiments on a thin aluminum plate with a thickness profile that varied radially in order to cause an effect resembling that of Maxwell's fish-eye lenses in optics. 7 They studied the imaging properties of this plate using a Gaussian pulse with central frequencies of 30 kHz and 60 kHz. They concluded that the refocusing time depends on the carrier frequency as a direct consequence of the dispersive nature of flexural waves in thin plates.…”
Section: Introductionmentioning
confidence: 99%